Management and security in the age of hyperconnectivity : 10th IFIP WG 6.6 International Conference on Autonomous Infrastructure, Management, and Security, AIMS 2016, Munich, Germany, June 20-23, 2016, Proceedings /: 10th IFIP WG 6.6 International Conference on Autonomous Infrastructure, Management, and Security, AIMS 2016, Munich, Germany, June 20-23, 2016, Proceedings. (2016) - Unknown
No abstract available